A CORRELATIONAL STUDY ON SELF-ESTEEM AND SELF-HARM BEHAVIOR AMONG UNDREGRADUATES IN KWARA STATE, Nigeria - Tiamiyu, Kamoru Abidoye; Adegbenro, Fadilat O.; Abdulkareem, Habibat Bolanle (Universitas Pendidikan Indonesia, 2024)
Self as become a Para- suicidal act among undergraduates in Nigeria Universities. Despite the enormous efforts of the government and the other educational stakeholders to eradicate this scourge, this challenge skyrockets day in and out. In order to proffer solution to this problem in a subjective manner, this study aimed at viewing self-esteem as a predictor of self-harm behaviour among undergraduates in Kwara State. Descriptive survey of correlational type was adopted for this research. Multistage random sampling technique was used to select 382 undergraduates from public and private universities in Kwara State. Two research instruments were used for data collection. They are Rosenberg Self-Esteem Scale (RSES) and Non-Suicidal Self-Injury Assessment Tool (NSSI-AT). Research questions were raised; main and operational hypotheses were formulated to guide this study. Descriptive statistics of frequency counts mean and percentages were used to answer the research questions while inferential statistics of Pearson Product Moment Correlation was used to test the generated research hypotheses at 0.05 level of significance. Results showed that there was significant relationship between self-esteem and self-harm behaviour among undergraduates in Kwara State (calculated r-value of 0. 657 critical value of .000).there was relative contributions of the dependent variables on self halm behaviour. Based on the findings, it was recommended that Government as well as other educational stakeholders should work harmoniously and supportive in boosting undergraduates self-esteem. KEYWORDS: self-esteem, self –harm, behaviour, undergraduates.